Apical ballooning in relatives. Issue 12 (16th November 2004) - Pison, L; De Vusser, P; Mullens, W
Abstract : Apical ballooning of the left ventricle was first introduced as takotsubo-like left ventricular dysfunction in 1990 by Satoh and colleagues. The syndrome is characterised by reversible extensive akinesia of the apical and mid-portions of the left ventricle with hypercontraction of the basal segment. For the first time two sisters with this syndrome are reported, suggesting a possible genetic aetiology.